Finite element analysis of hybrid energy harvesting of piezoelectric and electromagnetic - Muhammad Yazid, Muhammad Ammar Faris; Jamil, Norlida; Muhmed Razali, Nik Nurul Husna; Yusoff, A. R. (EDP Sciences, 2016)
Harvesting energy from ambient vibrations is a highly required method because of the wide range of available sources that produce vibration energy application from industrial machinery to human motion application. In this paper, the implementation of harvesting energy from two technologies to form a hybrid energy harvester system was analyzed. These two technologies involve the piezoelectric harvesting energy and the electromagnetic harvesting energy. A finite element model was developed using the Ansys software with the harmonic analysis solver to analyze and examine hybrid harvesting energy system. Both power output generated from the magnet and the piezoelectric is then combined to form one unit of energy. Further, it was found that the result shows the system generate the maximum power output of 14.85 μW from 100 Hz, 4.905 m/s2, and 0.6 cm3 for resonance frequency, acceleration, and the volume respectively from the optimal energy harvester design. Normalized Power Density (NPD) result of 10.29 kgs/m3 comparable with other literature also can be used in energy harvesting system for vibration application.